Fecal Steroid Profile of Female Javan Gibbons (Hylobates moloch) Maintained in Pairing-Typed Cage - Hera Maheshwari; Luthfiralda Sjahfirdi; Pudji Astuti; Bambang Purwantara; Hadi Sukardi Alikodra; Dondin Sajuthi; Reviany Widjajakusuma (HAYATI Journal of Biosciences, 2010)
Estrone conjugate (E1C) and pregnanediol glucuronide (PdG) were predominant steroid metabolites of estrogen and progesterone in feces of most primates and could be used to evaluate ovarian function. These metabolites were determined along with records of genital swelling throughout 3-4 months period from three female Javan Gibbons (Hylobates moloch) maintained in pairing-typed cage at Schmutzer Primate Center, Jakarta (Ullah) and at Taman Margasatwa Taman Sari, Bandung (Donna and Citah). Following methanolic extraction of lyophilized fecal powder, samples were analyzed using enzyme linked immunosorbent assay (ELISA) for E1C and PdG.  In all of the three females observed, both hormone profiles did not indicate any regular cycle of ovarian function even though genital swellings were sometimes observed. In one female (Donna) the hormone patterns showed clear signs of cycle irregularities with extended luteal phase of 40 days and erratic pattern of follicular phase. Of the other two females, no ovarian cycle was found. The data indicate that the fecal steroids analysis is a practical and valuable diagnostic tool for providing reliable information on ovarian function in Javan Gibbon. Factors affected reproductive hormonal profile should be taken in consideration in trying to achieve success in captive breeding program for this species.